La formación integral de los abogados: el ejercicio ético y su responsabilidad social (2020)
The family, the educational system, the human being and the State are an integral part in the process of the individuals’ formation. Principles and values are forged and based on the family as the fundamental nucleus. These principles and values will be strengthened in the academic training process, in this part, they get empowered and they will project some behaviors that will be implemented into the State institutions, private organizations and in all human relations. If the formation process gets disconnect from one of these chains, it will be an incomplete progress. This process shall not have the inputs required for achieving an ethical behavior, and this is one of the privileged guidelines of the society, and, for law professionals, furthermore, without those sufficient elements their behaviors could have disciplinarian objections. The aim is to generate a reflection regarding the role and commitment of the family and the State’s educational system in public education, and individuals in the private one, who have arranged for the training of children, students and professionals, from a starting point and ethical source, facing the evolution that social demands represent.